2013
DOI: 10.3329/pa.v19i2.16963
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rural Development Scheme of Islami Bank Bangladesh Limited on Beneficiaries in Mymensingh Sadar Area

Abstract: The present study was conducted to assess the impact of investment provided under "Rural Development Scheme" (RDS) of the "Islami Bank Bangladesh Limited" (IBBL) on the basis of using data collected from 25 respondents of each of group of investors, agriculture and business of the five selected villages in sadar upazila of Mymensingh district. Total household annual incomes were Tk. 59696 and Tk. 87332 respectively for the agriculture group and business group. The beneficiaries have increased their income (61 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Finally, the examination also recommends some approach rules for the smooth working and improvement of the interest as mentioned earlierfree MFI in any area like Bangladesh. Jinan et al (2008) found that after joining the RDS, there was a meaningful improvement in the expectation for the member family units' everyday comforts. Thirty-one percent of absolute credit got from RDS was used for horticultural purposes, 53 percent for business purposes, and 15 percent for family consumption on a normal.…”
Section: Selection Of the Study Areamentioning
confidence: 95%
“…Finally, the examination also recommends some approach rules for the smooth working and improvement of the interest as mentioned earlierfree MFI in any area like Bangladesh. Jinan et al (2008) found that after joining the RDS, there was a meaningful improvement in the expectation for the member family units' everyday comforts. Thirty-one percent of absolute credit got from RDS was used for horticultural purposes, 53 percent for business purposes, and 15 percent for family consumption on a normal.…”
Section: Selection Of the Study Areamentioning
confidence: 95%
“…In the research the dependent variable recovery depend on more independent variable like age, education, family size, business type and income. The regression form for the rate of recovery of rural credit is specified as: Income of the Debtor (X5) BDT (+) [34] Source: Author's Compilation, 2014…”
Section: Specification Of the Regression Modelmentioning
confidence: 99%
“…The micro finance investment system is being established an important impact in the form of increasing the income and reducing poverty style of the beneficiaries. It also helps potential women to be empowered in the society [19]. Ensuring access to credit in the rural areas for augmenting agricultural production, reducing poverty and improving the efficiency of the rural credit delivery system has been an area of focus in the planning process in our country [20].…”
Section: Introductionmentioning
confidence: 99%
“…Khan (2008), opined that "Shariah-compliant" issues are given less significance in microfinance applications even we work in a Muslim environment. Jinan et al (2008), in their research on the impact of RDS of IBBL on its beneficiaries in the Mymensingh Sadar area, found that the recipients have a substantial upward trend in their income (61 percent in agriculture and 89 percent in the business industry). According to estimates of Uddin, RDS has a notable positive impact on the fulfillment of the client"s food intake, education, education, taking clinical treatment, better clothes, the use of the toilet, using clean and pure consuming water, income and expenditure.…”
Section: Introductionmentioning
confidence: 99%